Phenolic Constituents from the Stems of Morus nigra and their α-Glucosidase Inhibitory Activities - Wang, Ling-Ling; Xu, Liang-Jin; Ma, Meng-Jie; Huang, Chun-Yue; Wu, Tong; Hu, Xiao (Pharmaceutical Fronts, 2021)
A new sanggenon-type flavanone, nigragenon F (1), together with 11 known compounds, trans-resveratrol (2), (E)-4-isopentenyl-3,5,2′,4′-tetrahydroxystilbene (3), notabilisin E (4), notabilisin A (5), morusin (6), petalopurpurenol (7), 8-geranyl-5,7-dihydroxycoumarin (8), 2,4-dihydroxybenzaldehyde (9), 4-ethoxy-2,6-dihydroxybenzoic acid (10), 3-hydroxy-4-methoxybenzaldehyde (11), and 4-hydroxybenzaldehyde (12), were isolated from the stems of Morus nigra. Compound 10 was a new natural product, compounds 3, 4, 7, and 8 were reported from the Morus genus for the first time. All of the isolated compounds were evaluated for their α-glucosidase inhibition activity. Among them, six compounds showed obvious inhibitory effects against α-glucosidase with IC50 values ranging from 1.24 to 19.00 µmol/L.
Keywords: Moraceae; Morus nigra; sanggenon-type flavanone; nigragenon F; α-glucosidase